2010
DOI: 10.1007/s00268-010-0875-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low‐dose Vasopressin on Trauma Outcome: Prospective Randomized Study

Abstract: This is the first trial to investigate the impact of vasopressin administration in trauma patients. Infusion of low-dose vasopressin maintained elevated serum vasopressin levels and decreased fluid requirements after injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 71 publications
1
58
0
1
Order By: Relevance
“…Following severe injury, patients may ultimately be shown to benefit from administration of a low dose of vasopressin and/or epinephrine to avoid the development of refractory shock states. 36,37 AUTHORSHIP S.M.C. contributed to the literature search, study design, data analysis, data interpretation, writing, and figures.…”
Section: Discussionmentioning
confidence: 99%
“…Following severe injury, patients may ultimately be shown to benefit from administration of a low dose of vasopressin and/or epinephrine to avoid the development of refractory shock states. 36,37 AUTHORSHIP S.M.C. contributed to the literature search, study design, data analysis, data interpretation, writing, and figures.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin has also been studied in a chart review and a weak RCT showing some benefit. 24,30 However, Collier et al 25 showed that the use of vasopressin was associated with increased mortality in their retrospective cohort analysis. A multi-centre RCT is currently in progress to assess the rate of admission to hospital, fluid requirements, hemodynamic variables, and rate of discharge in a population of traumatic refractory hemorrhagic shock patients treated with vasopressin or placebo.…”
Section: Statement: Epinephrine Increases Metabolic Abnormalities Commentioning
confidence: 99%
“…Rationale: The use of any vasopressor in the treatment of hemorrhagic shock in humans has been evaluated thus far in scattered case reports, four medical record reviews, one prospective cohort study, and one RCT. [24][25][26][27][28][29][30][31] Two negative studies 25,31 have shown an association with increased mortality in patients who received vasopressors, but the remaining studies show positive outcomes with respect to survival. Most studies involved the use of vasopressin 24,25,27,29,30 (see next section).…”
Section: Statement: Epinephrine Increases Metabolic Abnormalities Commentioning
confidence: 99%
“…In models of HS, vasopressin was comparably superior to fluid administration or epinephrine [42], [43] and has been proposed as the “preferred” vasopressor agent for hemodynamic stabilization during HS [41]. In a small clinical study in civilians suffering traumatic injury with hypotension, vasopressin infusion reduced the need of resuscitation fluids [44]. Clinicaltrials.gov lists two studies examining the effects of vasopressin in civilians with HS; the AVERT Shock study by Sims, C and the VITRIS study by Wenzel, V. [45].…”
Section: Discussionmentioning
confidence: 99%